Risk factors associated with severe disease in respiratory syncytial virus infected children under 5 years of age - Havdal, Lise Beier; Bøås, Håkon; Bekkevold, Terese; Bakken Kran, Anne-Marte; Rojahn, Astrid Elisabeth; Størdal, Ketil; Debes, Sara; Døllner, Henrik; Nordbø, Svein Arne; Barstad, Bjørn; Haarr, Elisebet; Fernández, Liliana Vázquez; et al. (Frontiers in Pediatrics, 2022)
Objective To evaluate risk factors for severe disease in children under 59 months of age hospitalized with respiratory syncytial virus (RSV) infection. Study design We prospectively enrolled 1096 cases of laboratory confirmed RSV infection during three consecutive RSV seasons in 2015-2018. Potential risk factors for severe disease were retrieved through patient questionnaires and linkage to national health registries. Need for respiratory support (invasive ventilation, bi-level positive airway pressure, or continuous positive airway pressure), and length of stay exceeding 72 hours were used as measures of disease severity. Associations were investigated using multivariable logistic regression analyses. Multiple imputation was used to avoid bias and inference induced by missing data. Results Risk factors associated with a need for respiratory support included age younger than 3 months of age (aOR: 12.5 (95% CI 2.11 to 73.8)), having siblings (aOR: 1.65 (95% CI 1.05 to 2.59)) and comorbidity (aOR: 2.40 (95% CI 1.35 to 4.24)). The length of hospital stay > 72 hours was significantly associated with being younger than 3 months of age (aOR: 3.52 (95% CI 1.65 to 7.54)), having siblings (aOR: 1.45 (95% CI 1.01 to 2.08)), and comorbidity (aOR: 2.18 (95% CI 1.31 to 3.61)). Sub-group analysis of children younger than 6 months of age confirmed the association between both young age and having siblings and the need for respiratory support. Conclusion In a large cohort of children < 59 months hospitalized with RSV infection, young age, comorbidity, and having siblings were associated with more severe disease. I